Visualizing complexity: an interactive web tool for mastering transformer equivalent circuits in engineering education - Mohamad Y. Abou Shahine; Hassan M. Karaky; Abdel-Mehsen A. Ahmad (Institute of Advanced Engineering and Science, 2026)
The analysis of transformer equivalent circuits remains a conceptually challenging topic in undergraduate electrical engineering, where students often struggle to connect abstract mathematical models with empirical data from open-circuit and short-circuit tests. This study aims to bridge this pedagogical gap by designing, developing, and evaluating a unified, web-based “transformer equivalent circuit and analysis tool” that facilitates real-time visualization of circuit parameters and voltage regulation. The research design employed an exploratory mixed-methods approach, utilizing a constructivist learning framework. The tool was integrated into an undergraduate curriculum where 25 electrical engineering students utilized the platform to process laboratory data. Evaluation was conducted using a structured questionnaire (Cronbach’s α=0.92) that assessed usability, conceptual understanding, and feature effectiveness, alongside qualitative feedback. Results indicated high perceived usability and a significant consensus that the tool clarified the relationship between theory and application. The implications of this study suggest that accessible, browser-based simulations serve as powerful supplementary resources that reduce extraneous cognitive load. By automating complex calculations and providing dynamic visual feedback, these tools effectively foster active learning and confidence in mastering complex engineering subjects, eliminating the barriers associated with traditional, high-complexity simulation software.